Potential for combining semantics and data analysis in the context of digital twins. (4th October 2021) - Vogel-Heuser, Birgit; Ocker, Felix; Weiß, Iris; Mieth, Robert; Mann, Frederik
Abstract : Modern production systems can benefit greatly from integrated and up-to-date digital representations. Their applications range from consistency checks during the design phase to smart manufacturing to maintenance support. Such digital twins not only require data, information and knowledge as inputs but can also be considered integrated models themselves. This paper provides an overview of data, information and knowledge typically available throughout the lifecycle of production systems and the variety of applications driven by data analysis, expert knowledge and knowledge-based systems. On this basis, we describe the potential for combining data analysis and knowledge-based systems in the context of production systems and describe two feasibility studies that demonstrate how knowledge-based systems can be created using data analysis. This article is part of the theme issue 'Towards symbiotic autonomous systems'.